INTEGRAL ASSESSMENT OF THE LEVEL OF PROVISION OF STRATEGIC MANAGEMENT OF INNOVATIVE DEVELOPMENT OF THE ENTERPRISE - Salman Altfihat, Ali; Alexey Alexeyevich, Kuzubov; Aleskandr Nikolaevich, Maksimenko (Revista Inclusiones, 2020)
The article demonstrates the results of a study of the process of the comprehensive assessment of the enterprise innovative development embeddedness level into strategic management based on the methodology of a multipurpose analysis of decision-making situations in conditions of uncertainty, conflict and risk. There was formed a system of generalized and partial indicators of the enterprise functioning affecting the level of its innovative development, including: a subsystem of generalized assessment of the state of organizational, technical and economic development of the enterprise; a subsystem of effective quality indicators for assessing the level of strategic management of an innovative enterprise development; a subsystem for determining the results of the situations, events, facts and reflecting the results of alternative options for enterprise management in conditions of uncertainty and change.